Leadership 5.0: Towards a Post Normal Era - Tanti Widia Nurdiani (Jurnal Pengabdian Masyarakat Formosa, 2022)
The COVID-19 pandemic has impacted numerous aspects of life. The effects of industrial revolution 4.0 and society 5.0 bring new chances for Indonesia as it enters the post-normal age. For Indonesia, a revolution that stresses digital economic growth is beneficial. Mrs. Tanti Widia Nurdiani, director of Smart Indonesia Academy, was invited by DPK Perbarindo Malang Raya to conduct a leadership 5.0 workshop for all BPR BPRS in the Perbarindo Malang Raya Region. This form of training is a community-empowerment-focused activity. This approach to community empowerment intends to enhance leadership 5.0 for BPR BPRS throughout the Perbarindo Malang Raya Region. This is a qualitative research method with an analytical descriptive approach. This study focuses on the training offered by Smart Indonesia Academy to BPR BPRS in the Perbarindo Malang Raya Region. Smart Indonesia Academy successfully performed a community service project on May 21, 2022, at the Atria Hotel & Conference, which was attended by BPR BPRS members from the entire Perbarindo Region and Malang Raya. The Smart Indonesia Academy has prioritized leadership 5.0 knowledge.